1991
DOI: 10.2466/pms.1991.73.3.943
|View full text |Cite
|
Sign up to set email alerts
|

Students' Perceptions of Male Teachers: Effects of Teachers' Dress and Students' Characteristics

Abstract: The purpose of this study was to explore the effects of a male teacher's clothing and selected students' characteristics on students' perceptions of teachers' characteristics. The sample consisted of 152 male and female high school students. Respondents selected one of four photographs of a male teacher model dressed in four different clothing styles for each of 20 teachers' characteristic statements. The mediating effects of students' gender, formality of clothing, and perceptions of the importance of clothin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
0
7
1
Order By: Relevance
“…Unlike the results from Butler and Roesel's [30] study, students in this study did not see casually dressed teachers as any more socially attractive than more formally dressed teachers. This may be due in part to business orientation of both the students and class that they were in.…”
Section: Clothing and Teacher Attractivenesscontrasting
confidence: 56%
See 2 more Smart Citations
“…Unlike the results from Butler and Roesel's [30] study, students in this study did not see casually dressed teachers as any more socially attractive than more formally dressed teachers. This may be due in part to business orientation of both the students and class that they were in.…”
Section: Clothing and Teacher Attractivenesscontrasting
confidence: 56%
“…Butler and Roesel [30] acknowledge that this has the effect of ensuring the perceiver's attention to clothing. However, this method comes at the cost of mundane realism.…”
Section: Overview Of Present Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, adults view individuals dressed casually such as wearing jeans and a t-shirt as less knowledgeable than those dressed more formally such as wearing a suit. In contrast, they view more formally dressed individuals as authority figures that resemble teachers and are more knowledgeable [ 21 ]. In addition, women tend to rate individuals in formal business clothing more positively on a range of traits such as intelligence, wealth, likeability, and trustworthiness [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that students judged casually dressed teachers as more approachable, but less knowledgeable than formally dressed teachers. In a follow-up study, Butler and Roesel (1991) found similar results for male teacher models. Lukavsky et al (1995) extended this research, showing that casually dressed teachers were perceived as more approachable and flexible, yet elicited ratings of less respect than formally dressed instructors.…”
mentioning
confidence: 57%